Financial Imbalances, Crisis Probability and Monetary Policy in Norway - Ragna Alstadheim; Ørjan Robstad; Nikka Husom Vonen (Norges Bank, 2017)
We assess the strength of the impact of a monetary policy shock on financial crisis probability in Norway. Policy effects go via the interest rate impact on credit, house prices and banks' wholesale funding. We find that the impact of a monetary policy shock on crisis probability is about 10 times larger than what previous studies suggest. The large impact is mostly due to a fall in property prices and banks' wholesale funding in response to a contractionary monetary policy shock. In contrast, and in line with existing literature, there is a more limited contribution to reduced crisis probability from the impact of monetary policy on credit.
hdl:11250/2495546
Keywords: 330; structural VAR; financial imbalances; financial crisis; monetary policy; E32; E37; E44; E52